Friends. The complete fifth season [videorecording (DVD)] - Aniston, Jennifer; Cox, Courteney, 1964-; Kudrow, Lisa; LeBlanc, Matt; Perry, Matthew, 1969-; Schwimmer, David, 1966- (Warner Bros. Entertainment : Distributed by Warner Home Video, 2010)
Continuing fifth season episodes of the smash-hit television comedy series, documenting the lives and loves of six pals in New York City.